Flavones Produced by Mulberry Flavone Synthase Type I Constitute a Defense Line against the Ultraviolet-B Stress - Han Li; Dong Li; Zhen Yang; Qiwei Zeng; Yiwei Luo; Ningjia He (Plants, 2020)
Flavones, one of the largest classes of flavonoids in plants, have a variety of bioactivities and participate in the resistance response of plants to biotic and abiotic stresses. However, flavone synthase (FNS), the key enzyme for flavone biosynthesis, has not yet been characterized in mulberry. In this study, we report that the leaves of certain mulberry cultivars, namely BJ7, PS2, and G14, are rich in flavones. We identified a Fe2+/2-oxoglutarate-dependent dioxygenase from Morus notabilis (MnFNSI) that shows the typical enzymatic activity of a FNSI-type enzyme, and directly converts eriodictyol and naringenin into their corresponding flavones. Overexpression of MnFNSI in tobacco increased the flavones contents in leaves and enhanced the tolerance of tobacco to ultraviolet-B (UV-B) stress. We found that mulberry cultivars with higher flavones contents exhibit less UV-B induced damage after a UV-B treatment. Accordingly, our findings demonstrate that MnFNSI, a FNSI-type enzyme, is involved in the biosynthesis of flavones, which provide protection against UV-B radiation. These results lay the foundation for obtaining mulberry germplasm resources that are more tolerant to UV-B stress and richer in their nutritional value.